(untitled) (Journal of Asian Development Studies, 2025)
The study refers to the varying role of language in constructing meanings differently across different registers. Semantic diversity refers to manifold meanings and multiple interpretations of language within different domains. This study reveals the presence of semantic diversity within the fields of Information Technology (IT), Judiciary, and Medicine, highlighting the divergent meanings, terminologies, and linguistic features. Each of these domains has established its conventions, specialized vocabulary, and contextual nuances. The analysis explores significant diversity encountered within these registers, and how professionals in these domains understand and convey information, while also elucidating the chances of miscommunication. Through qualitative and quantitative analysis, the study aims to explore the impact of semantic diversity on communication between experts and non-experts. The findings have implications of this semantic diversity for pedagogical approaches, Natural Language Processing (NLP) and promoting effective language understanding. This paper presents the objectives, targets, and methodologies for an inclusive analysis of the linguistic variabilities and features by focusing on the registers of Medicine, IT, and Judiciary.